3DQRS: A method to obtain reliable QRS complex detection within high field MRI using 12‐lead electrocardiogram traces. Issue 4 (22nd January 2014) - Gregory, T. Stan; Schmidt, Ehud J.; Zhang, Shelley Hualei; Ho Tse, Zion Tsz
<x xml:space="preserve">Abstract</x> Purpose To develop a technique that accurately detects the QRS complex in 1.5 Tesla (T), 3T, and 7T MRI scanners. Methods During early systole, blood is rapidly ejected into the aortic arch, traveling perpendicular to the MRI's main field, which produces a strong voltage (VMHD) that eclipses the QRS complex. Greater complexity arises in arrhythmia patients, since VMHD varies between sinus‐rhythm and arrhythmic beats. The 3DQRS method uses a kernel consisting of 6 electrocardiogram (ECG) precordial leads (V1‐V6), compiled from a 12‐lead ECG performed outside the magnet. The kernel is cross‐correlated with signals acquired inside the MRI to identify the QRS complex in real time. The 3DQRS method was evaluated against a vectorcardiogram (VCG)‐based approach in two premature ventricular contraction (PVC) and two atrial fibrillation (AF) patients, a healthy exercising athlete, and eight healthy volunteers, within 1.5T and 3T MRIs, using a prototype MRI‐conditional 12‐lead ECG system. Two volunteers were recorded at 7T using a Holter recorder. Results For QRS complex detection, 3DQRS subject‐averaged sensitivity levels, relative to VCG were: 1.5T (100% versus 96.7%), 3T (98.9% versus 92.2%), and 7T (96.2% versus 77.7%). Conclusion The 3DQRS method was shown to be more effective in cardiac gating than a conventional VCG‐based method. Magn Reson Med 71:1374–1380, 2014. © 2014 Wiley Periodicals, Inc.